Relationship of Myofibrillar Fragmentation Index to Warner-Bratzler Shear Force and Palatability Tenderness of Longissimus Lumborum and Semitendinosus Steaks - L. L. Prill; K. J. Phelps; J. M. Gonzalez; T. A. Houser; E. A. Boyle; T. G. O'Quinn (Kansas Agricultural Experiment Station Research Reports, 2018)
Objective:The objective of this study was to determine the relationship between the myofibrillar fragmentation index, Warner-Bratzler shear force and sensory traits oflongissimus lumborum(strip loin), and thesemitendinosus(eye of round) steaks. Study Description:Forty beef strip loins and 40 eye of rounds were collected, divided into anatomical location, and cut into steaks. Steaks used for Warner-Bratzler shear force and sensory panel review were cooked to 160°F. For Warner-Bratzler, six 1-in cores were sheared with a Warner-Bratzler shear head. Sensory steaks were served to panelists trained according to American Meat Science Association guidelines for sensory evaluation. Procedures described by Culler et al. (1978) were used to determine myofibrillar fragmentation index. The Bottom Line:The correlation between myofibrillar fragmentation index, Warner-Bratzler shear force, and sensory measures of tenderness were weak, indicating myofibrillar fragmentation index was not a reliable indicator of beef tenderness for the muscles evaluated.
Keywords: beef; myofibrillar fragmentation index; tenderness